Contemporary findings in genetic studies with respect to the sport talent selection - Kovar, R.
1. The results from genetic studies show that the share of heredity influence in the variability of some somatic traits and motor and sport abilities is relatively great. Thus in these cases individual genotypic presuppositions are the main cause of a different motor and sports level of individuals living in an identical environment. 2. From the point of view of sports talent selection it is very important to know, which of the somatic traits and motor abilities are more or less genetically determined - the probability of a right prediction on the basis of traits and properties with more significant heritability is much higher, on the other hand, properties and functions with a low heritability might be more influenced by an intentional training load. 3. Individual genotype presuppositions and the share of heredity in the performance ought to be respected in sport practice. Nevertheless, maximum motor development and top sport level are not possible without optimum environment conditions and a corresponding activity of the subject. That is why individual genotype presuppositions and the process of ensuring optimum conditions should always be in correct relation.